2022
DOI: 10.3390/nu15010060
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Leong et al. Comment on “Hosseini et al. Effects of Vitamin D Supplementation on COVID-19 Related Outcomes: A Systematic Review and Meta-Analysis. Nutrients 2022, 14, 2134”

Abstract: We thank Drs. Leong et al. for their comments [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…The copyright holder for this preprint this version posted April 1, 2024. ; https://doi.org/10.1101/2024.03.30.24305112 doi: medRxiv preprint acupuncture therapy, 34 acupressure, 35 aromatherapy, 17 exercise, 23 TENS, 36 physiotherapy, 37 psychological intervention, 20 manual therapy, 38 moxibustion, 39 nutritional therapy, 25 non-invasive brain stimulation, used as treatment will be included. 40 No restrictions will be placed on the intervention timing (pre-menstrual, menstrual period, post-menstrual), courses, or delivery form (researchers, self, or device).…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…The copyright holder for this preprint this version posted April 1, 2024. ; https://doi.org/10.1101/2024.03.30.24305112 doi: medRxiv preprint acupuncture therapy, 34 acupressure, 35 aromatherapy, 17 exercise, 23 TENS, 36 physiotherapy, 37 psychological intervention, 20 manual therapy, 38 moxibustion, 39 nutritional therapy, 25 non-invasive brain stimulation, used as treatment will be included. 40 No restrictions will be placed on the intervention timing (pre-menstrual, menstrual period, post-menstrual), courses, or delivery form (researchers, self, or device).…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…Further lowering the cost of the overall network solution is possible via selectively deploying optical amplifiers and customizing the power splitters/combiners. The optimization framework described in [14] to achieve this objective while respecting physical constraints (e.g., receiver sensitivity, maximum launch power for negligible nonlinear impairments, maximum power unbalance between SCs at the hub's receiver) shows that the number of optical amplifiers can be halved (see Fig. 5), which further adds to the benefits of replacing P2P by P2MP transceivers.…”
Section: Leveraging the Potential Of P2mp Coherent Pluggable Opticsmentioning
confidence: 99%
“… Long-term cost-effectiveness and environmental impact of P2MP transceivers: in addition to the benefits against state-of-the-art P2P coherent pluggable transceivers, it is paramount to demonstrate that P2MP transceivers are expected to remain cost-effective in the long-term. The study reported in [15] considers a metro-aggregation network evolving over a 5-year period, with the introduction of higher capacity transceivers and modelling different planning strategies that account for varying degrees of confidence on earlier traffic predictions. The results provide evidence that CAPEX reductions from using P2MP instead of P2P transceivers are typically in the range of 30% and remain above 20% even in the scenarios more favorable to P2P transceivers.…”
Section: Leveraging the Potential Of P2mp Coherent Pluggable Opticsmentioning
confidence: 99%
“…[6] In recent years, it is shown that subclinical Vitamin D deficiency causes infectious, autoimmune, and cardiovascular diseases, obesity, depression, impaired glycemic index, COVID-19, and various types of cancer. [7][8][9][10] Vitamin D2 (ergocalciferol) and Vitamin D3 (cholecalciferol) are the two major isoforms. Ergosterol is converted to Vitamin D3 by UVB light.…”
Section: Introductionmentioning
confidence: 99%